2013
DOI: 10.1158/1078-0432.ccr-12-2895
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Niclosamide in Human Glioblastoma

Abstract: Purpose: Glioblastoma is a highly malignant, invariably fatal brain tumor for which effective pharmacotherapy remains an unmet medical need.Experimental Design: Screening of a compound library of 160 synthetic and natural toxic substances identified the antihelmintic niclosamide as a previously unrecognized candidate for clinical development. Considering the cellular and interindividual heterogeneity of glioblastoma, a portfolio of short-term expanded primary human glioblastoma cells (pGBM; n ¼ 21), common gli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 48 publications
(59 reference statements)
5
124
0
5
Order By: Relevance
“…Some of them were previously suggested as therapeutic candidates for GBM as single agents such as Doxorubicin hydrochloride, 21 Camptothecine (S,C), 22 Proscillaridin A, 15 Pyrivinium pamoate, 23 and Niclosamide. 24 We report Alexidine dihydrochloride, Monensin sodium salt, Lanatoside C, Digitoxigenin, Digoxigenin, Digoxin, Quinacrine dihydrochloride, Terfenadine and Astemizole as novel drugs that can be therapeutic candidates for GBM. Notably, we did not identify Temozolomide (TMZ), the most common drug used as anti-GBM therapy, 2,25 as an effective agent in our screen although it was included, attesting to the unmet need for identifying novel drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were previously suggested as therapeutic candidates for GBM as single agents such as Doxorubicin hydrochloride, 21 Camptothecine (S,C), 22 Proscillaridin A, 15 Pyrivinium pamoate, 23 and Niclosamide. 24 We report Alexidine dihydrochloride, Monensin sodium salt, Lanatoside C, Digitoxigenin, Digoxigenin, Digoxin, Quinacrine dihydrochloride, Terfenadine and Astemizole as novel drugs that can be therapeutic candidates for GBM. Notably, we did not identify Temozolomide (TMZ), the most common drug used as anti-GBM therapy, 2,25 as an effective agent in our screen although it was included, attesting to the unmet need for identifying novel drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Sack et al (5) screened 1,280 types of pharmaceutically active compounds using high-throughput screening technology and found niclosamide was able to inhibit colon cancer metastasis. Recently, Wieland et al (6) found that niclosamide is cytotoxic, inhibits cell migration and enhances the effects of chemotherapeutic drugs in glioma cells. Another study (7) found that niclosamide inhibits the growth and induces apoptosis of acute myeloid leukemia cells in vitro and in nude mice, while cells from normal bone marrow were spared.…”
Section: Introductionmentioning
confidence: 99%
“…Niclosamide was originally developed for the treatment of tapeworm infection and is clinically used worldwide (14,15 (18) and inhibition of the canonical Wnt signaling pathway (19). Niclosamide also downregulates the expression of cyclin D1, one of the target molecules of the Wnt pathway, via glycogen synthase kinase-3β (17,20).…”
Section: Introductionmentioning
confidence: 99%